The iPad in the K12 classroom: Implementation and professional development support for integrating digital storytelling activities - Ostashewski, Nathaniel; Reid, D. (The Educational Computing Association of Western Australia Inc. (ECAWA), 2012)
This paper presents successes and challenges of an iPad implementation project in five rural K-12 classrooms. A need to connect what was happening in these schools, with regards to supporting 21st Century skills integration, to the larger community had been identified. The incorporation of digital storytelling activities supported by iPad2 technology into classroom practice was identified as a pedagogical implementation that could, over time, meet this need. Classrooms involved in this project were provided with: a “teacher” iPad2, 4-8 “student” iPad2s, digital storytelling Apps and iTunes accounts, face-to-face professional development sessions, socially networked professional development support, and direct classroom activity support during the first half of a school year. A key finding is that in order for digital storytelling to be successful in the classroom, a simple repeatable workflow for story creation is required. Other findings include teacher insights regarding mobile technology, engagement of students with iPad2 devices, use of mobile apps, and challenges with device management. Further research on how to support teacher sharing at a distance as well as developing a learning community for technology implementation is needed. Additionally, further examination of the theories underscoring strategies meant to tie communities to school and 21st Century curriculum is needed.